Russian nonverbal communication in teaching representatives of different cultures - Radif R. Zamaletdinov; Galina S. Kalinina; Gulshat Kh. Zinnatullina (Russian Language Studies, 2025)
The study studies Russian gestures in teaching Russian as a foreign language. Gesture communication is an important nonverbal interaction in various cultures and languages. The relevance of the study stems from the importance of nonverbal communication in teaching Russian to foreigners, the need to identify specific Russian gestures, their semantics, and cultural peculiarities and to analyze how these gestures correlate with verbal communication means in Russian culture. The aim of the study is to provide a scientific description of the specific gesture communication within Russian speech etiquette, including its meaning and contextual application and the corresponding difficulties for foreign students learning Russian. The research material is data from a 2023-2024 online survey in Google Forms. The questionnaire was aimed at studying perception and interpretation of Russian gestures by international students. The first block of the questionnaire is an open question “What is difficult for you when interpreting Russian gestures?”. It gave qualitative data on individual problems in understanding nonverbal components of Russian communication. The second block contains a series of visual tasks with pictures of Russian gestures typical for different communication intensions and variants of their semantic interpretation. The students must choose the correct or the most relevant answer. The complex approach helped to collect declarative information on difficulties and practical results on the ability to correctly identify Russian gestures in intercultural communication. The research methods include theoretical analysis for gesture definitions and approaches to their studying; quantitative content analysis for classification and statistical estimation of the collected data on Russian, Tatar, and Arab gesture communication; linguistic observation of the real gestures used by the representatives of different cultures. The students were regularly observed in classroom and at cultural events at Kazan universities for six years (2019-2024). This gave a comprehensive and representative data on using gestures in intercultural communication. The locations made it possible to analyze gesture activity in different cultural contexts. Universal and specific means of nonverbal communication have been determined, and specific gestures used in Russian, Arab, and Tatar cultures and their corresponding situations are discussed. Significant differences in gestures of Tatar and Arab students learning Russian have been identified; precise and controlled gestures prevail in formal situations, whereas informal situations reveal greater gestural diversity, including expressive and emotional aspects. The findings are useful for teaching Russian as a foreign language, in intercultural communication courses, and in adapting foreign specialists to work in Russia.